Bookkeeping for dummies - Kelly, Jane; Barrow, Paul; Epstein, Lita (West Sussex, England : John Wiley & Sons, 2011)
Accurate bookkeeping is crucial to every business - but few people relish the task. This straight-talking guide simplifies every aspect of financial record keeping, walking you through all the basic skills you need. From tracking transactions and keeping ledgers to producing balance sheets and year-end reports, this book makes bookkeeping your best friend in business.
Part 1. Basic Bookkeeping: why you need it -- Part 2. Keeping a paper trail -- Part 3. Recording day-to-day business operations -- Part 4. Preparing the books for year-end -- Part 5. Reporting result and starting over -- Part 6. The part of tens.
Includes index.
Keywords: BOOKKEEPING